Enhancement of Seismic reflectors by using VSP and Seismic Inversion in Sindbad oil field, south of Iraq - Doohee, Osama Salam; AL- Rahim, Ali M. (Iraqi Journal of Science, 2018)
The purpose of this research is to enhance the methods of surface seismic data processing and interpretation operations by using the produced information of vertical seismic profile (measured velocity and corridor stack). Sindbad oil field (South of Iraq) is chosen to study goals and it’s containing only one well with VSP survey (Snd2) that covering depth from Zubair to Sulaiy Formations and 2D seismic lines of Basrah Survey. The horizons were picked and used with low frequency contents from well data for the construction of low frequency model and it was used with high frequency of VSP to make the high frequency model that compensated to seismic main frequency through inversion process. Seismic inversion technique is performed on post stack of 2D seismic data (2Br2) through Hampson-Russell CGG program. The inversion model of low frequency shows 88.5% matching with relative seismic impedance while high frequency model 93.3% matching with lower error percent. The two impedance sections which resulted from inversion model were convoluted with best wavelet from VSP data to make a new seismic section. The LFM section was similar to original seismic section while the HFM section shows real enhancement of the Flatspot (DHI) feature and recoverable some missing reflectors.